Veronica Mars. The complete second season [videorecording (DVD)] - Bell, Kristen, 1980-; Daggs, Percy; Dunn, Teddy (Warner Home Video, 2013)
In season two, the Mars family find themselves embroiled in another season-long mystery hitting closer to home following a new local tragedy. Veronica must also deal with her increasingly complicated romantic life and a whole new school year.